2013
DOI: 10.1149/2.017401jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Exchange Kinetics of (Bi,Sr)(Co,Fe)O3-δThin-Film Microelectrodes

Abstract: Mixed-conducting (Bi,Sr)(Co,Fe)O 3-δ (BiSCF) perovskites are considered to be promising candidates for the application as cathode materials in solid oxide fuel cells (SOFCs) operating in the intermediate-temperature regime. In this study, the effective rate constants of surface oxygen exchange of both Co-free and Co-containing BiSCF perovskites were measured by electrochemical impedance spectroscopy (EIS) on geometrically well-defined thin-film microelectrodes on Y 2 O 3 -doped ZrO 2 (YSZ) single crystal subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
(124 reference statements)
1
13
0
Order By: Relevance
“…Such correlation, however, is not valid for the whole of the materials. These are also consistent with the previous studies (13,15,19).…”
Section: Resultssupporting
confidence: 94%
“…Such correlation, however, is not valid for the whole of the materials. These are also consistent with the previous studies (13,15,19).…”
Section: Resultssupporting
confidence: 94%
“…Bismuth ferrate BiFeO3 (BFO) is base for the perovskite solid solutions Bi1-xSrxFeO3-δ and Bi1-xSrxFe1-yCoy O3-δ , which were recently also proposed as promising cathodes for SOFCs. [2][3][4][5] In the same time BFO continues to attract considerable attention due to its multiferroic properties 6 at ambient conditions. It has also been found that photocatalytic 7 and photovoltaic 8 properties of BFO are enhanced due to its ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the conductivity and ORR capability, Co [18,21], Ca [19] and Mn [20] were doped in the BSF perovskite structure. Besides, a higher oxygen exchange rate of pore-free BSF was reported, even higher than that of (La,Sr)FeO 3−δ .…”
Section: Introductionmentioning
confidence: 99%
“…A new cathode material based on (Bi,Sr)FeO 3 (BSF) was synthesized and reported with interesting conductivity [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. To enhance the conductivity and ORR capability, Co [ 18 , 21 ], Ca [ 19 ] and Mn [ 20 ] were doped in the BSF perovskite structure. Besides, a higher oxygen exchange rate of pore-free BSF was reported, even higher than that of (La,Sr)FeO 3−δ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation